THE INFLUENCE OF CLASSROOM ENVIRONMENT ON STUDENT ENGAGEMENT AND MOTIVATION (Conferencea, 2024)
“They may forget what you said but they will never forget how you made them feel" (Carl W. Buehner, 1971). This research investigates the role of the teachers in creating the classroom environment and its influence on student engagement and motivation. The study investigates the case of students at Kimyo International University in Tashkent and implements surveys and classroom observations to gather data. The findings suggest that teachers play a key role in creating classroom environments that promote student engagement and motivation, creating a positive and supportive learning environment, and building rapport with students. Respondents also claimed positive influence by teacher’s establishing appropriate classroom layouts, controlling level of noise and using visual aids, tools, providing positive reinforcement, and using assertive discipline techniques. The study concludes that teachers are the creators of a positive and productive learning environment that promote students’ active participation and increased desire to learn.